2013
DOI: 10.1371/journal.pone.0060317
|View full text |Cite
|
Sign up to set email alerts
|

miR-146a Inhibits Cell Growth, Cell Migration and Induces Apoptosis in Non-Small Cell Lung Cancer Cells

Abstract: Aberrant expression of microRNA-146a (miR-146a) has been reported to be involved in the development and progression of various types of cancers. However, its role in non-small cell lung cancer (NSCLC) has not been elucidated. The aim of this study was to investigate the contribution of miR-146a to various aspects of the malignant phenotype of human NSCLCs. In functional experiments, miR-146a suppressed cell growth, induced cellular apoptosis and inhibited EGFR downstream signaling in five NSCLC cell lines (H35… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
250
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 231 publications
(262 citation statements)
references
References 44 publications
10
250
2
Order By: Relevance
“…Our findings further indicate that inhibition of miR-181a in leukemia cells impacted their susceptibility to NKmediated lysis. Although emerging studies indicate the potential involvement of miR-146a in cell proliferation and drug resistance, 44,45 blocking miR-146a in our experimental model had no effect on NK-cell mediated lysis. Therefore, we hypothesized that miR-146a is involved in the molecular mechanisms that contribute to drug resistance but not to resistance to NK-mediated lysis.…”
Section: Discussioncontrasting
confidence: 58%
“…Our findings further indicate that inhibition of miR-181a in leukemia cells impacted their susceptibility to NKmediated lysis. Although emerging studies indicate the potential involvement of miR-146a in cell proliferation and drug resistance, 44,45 blocking miR-146a in our experimental model had no effect on NK-cell mediated lysis. Therefore, we hypothesized that miR-146a is involved in the molecular mechanisms that contribute to drug resistance but not to resistance to NK-mediated lysis.…”
Section: Discussioncontrasting
confidence: 58%
“…Our group previously found that TRAF6 functions as a bridge between miR-146a and the NF-kB pathway in NSCLC (Chen et al, 2013c). Besides miR-146a, TRAF6 has been proved to be the target genes for miR-125a (Guo et al, 2014) and miR-125b (Wang et al, 2014).…”
Section: Traf6 Expression Is Associated With Lung Cancer Progressionmentioning
confidence: 98%
“…In China, lung cancer is the first leading cause of death from all cancers (Chen et al,additional therapy. However, the specific markers have not been achievable (Chen et al, 2012;Chen et al, 2013a;2013b;2013c;Gazala et al, 2013;Granger et al, 2013). Therefore, the research for effective molecular markers for diagnosis and treatment of lung cancer is an important issue at present.…”
Section: Introductionmentioning
confidence: 99%
“…Nonsmall cell lung cancers are the most common variety, accounting for 80%‐85% of new LC cases. Approximately, 70% of NSCLCs patients are diagnosed at an advanced stage with the tumor already being metastasized and its 5‐year survival rate is about 16% 9. Therefore, it is urgent to explore the exact molecular processes involved in the development of NSCLCs and to achieve potential therapeutic targets.…”
Section: Hoxa11‐as Lncrna In Human Cancersmentioning
confidence: 99%